The Genetic Architecture of Grain Yield in Spring Wheat Based on Genome-Wide Association Study - Li, Yuyao; Tang, Jingquan; Liu, Wenlin; Yan, Wenyi; Sun, Yan; Che, Jingyu; Tian, Chao; Zhang, Hongji; Yu, Lihe (Frontiers in Genetics, 2021)
Uncover the genetic architecture for grain yield (GY) related traits are important for wheat breeding. To detect stable loci for GY related traits, a genome-wide association study (GWAS) was conducted in a diverse panel, which including 251 elite spring wheat accessions mainly from the Northeast of China. In total, 52,503 SNPs from the wheat 55 K SNP arrays were used. Thirty-eight loci for GY related traits were detected and each explained 6.5-16.7% of the phenotypic variations. Among which, 12 are at the similar locations with the known genes or quantitative trait loci (QTL), and 26 are likely to be new. Furthermore, 6 genes possibly involved in the cell division, signal transduction and plant development as candidate genes for GY related traits. This study provides new insights into the genetic architecture of GY and the significantly associated SNPs and accessions with a larger number of favorable alleles could be used to further enhance GY in breeding.